GRAPHIC NOVEL: INTRODUCTION, HISTORY AND FUTURE IN INDIAN SUBCONTINENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
Graphic novel is 21st century novel. Richard Kyle coined the term graphic novel first time in a magazine named Capa-alpha. The Dictionary Merriam Webster gives a proper definition of graphic novel, ‘Call it a fictional story that is presented in a comic strip format and publish in a book’. The word graphic novel is used in border term because it includes fiction, non-fiction and anthologizes books. Graphic novels are different from comic books. There is a difference between a book in normal language and a book with images Graphic novel is better than the text book because it better depict a particular idea or scene. It uses the interplay of text, images and illustrations in a comic strip format to tell a story. To construct a narrative, graphic novel uses graphic elements such as panels, frames, speech, and thought balloons etc. instead of depending on text only. It uses these graphic devices in a sequential way to create and evoke a story in a reader’s mind. Graphic novels are not glorified comic book; they are novels using images as well as words to tell a story. In comic books images give an overview of the story which encourages the child to read the whole book. Graphic novels contain high level vocabulary than comic books. Graphic novels are great for visual learners. It offers the opportunity to learn important reading skills like inferences than text books because they depict an idea or a scene in a better way.